Multiple Dimensions of Non-western Rhetoric: A Systematic Review of the Literature - Baral, Raj Kumar (The Batuk, 2024)
This systematic review explores publication trends and thematic coverage of non-western rhetoric in the last fifty years. Amidst growing interest, non-western rhetoric being underexplored prompts this article to identify research gaps and offer insights for future studies. Articles reviewed in this paper reveal that issues like resistance against western rhetorical dominance and countering orientalist perspectives, alongside translation’s role and unique features inherent in the non-west have occupied some space. Unexamined or underexamined areas vis-à-vis non-western rhetoric include environment, indigeneity, power dynamics, cultural context, identity intersections, and socioeconomics. Similarly, other underexplored aspects include modern media, digital communication, oral tradition’s adaptation, social justice rhetoric, and religion’s impact on the rhetoric of Bharatavarsha.